Историја на проучување нa македонското епиграфско богатство од страна на руските научници - Marija Paunova (УКИМ, Филолошки факултет Блаже Конески, 2024)
This article examines the contribution of Russian editions in affirmation of Mаcedonian epigraphic wealth. We stress on eminent surdes, editions od Russian scientists in which are published, documented and interpreted epigraphic monuments from Macedonia.
Keywords: Slavic epigraphy, studies, Macedonia, Russian scientist